The Role of the Management Accounting System and Decision-Making Style on Managerial performance - Efendi, David; Kusuma, Emeralda Ayu (University of Merdeka Malang, 2021)
This study aimed to provide empirical evidence on the relationship between the management accounting system (MAS) and decision-making style on cooperatives' managerial performance in Ponorogo. Data were collected from 119 questionnaires, while 60 questionnaires could be analyzed. Then, SPSS was applied to test non-response bias and descriptive statistics. SmartPLS was used for hypothesis testing. Research findings indicated that MAS did not affect managerial performance, and the decision-making style affected managerial performance.DOI: https://doi.org/10.26905/jkdp.v25i1.5330